Potensi Berbagai Jenis Kompos Produk Samping Pertanian dalam Meningkatkan Populasi Azotobacter, C-Organik, N-Total Tanah, dan Hasil Tanaman Tomat pada Inceptisols - Setiawati, Mieke Rochimi; Iskariman, Ahlan Azman; Suryatmana, Pujawati; Kamaluddin, Nadia Nuraniya (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Inceptisols hs a potential to be developed as a growth medium for tomato cultivation. The low to moderate fertility of Inceptisols can be improved by applying compost derived from various types ofagricultural waste, which can increase soil organic matter content, support the growth of nitrogenfixingrhizosphere microbes such as Azotobacter sp., enhance soil fertility, and ultimately improvetomato yield. This study aimed to analyze the effects of different types and application dosage ofagricultural waste compost on the population of Azotobacter sp., soil organic carbon, total nitrogen,and the yield of tomato plants (Lycopersicum esculentum Mill.) grown on Inceptisols. A greenhousepot experiment was conducted with a Randomized Complete Block Design with ten treatments andthree replication, consisted of control (no compost) and three types of compost (rice straw, sugarcanebagasse, and empty oil palm fruit bunches) applied at rates of 10, 15, and 20 tons ha⁻¹. Theexperimenal result showed that agricultural waste compost significantly increased the population ofAzotobacter sp., soil organic carbon content, and tomato yield, but had no significant effect on totalsoil nitrogen. The application of rice straw compost at a dosage of 20 tons ha⁻¹ was the most effectivetreatment to increase Azotobacter sp. population, fruit weight, and the number of tomato fruits perplant.